Choroidal schwannoma: a case series of five patients. Issue 8 (23rd April 2014) - Damato, Bertil; Damato, Erika M; Konstantinidis, Lazaros; Heimann, Heinrich; Coupland, Sarah E
Abstract : Aim: To report a case series of five patients diagnosed with choroidal schwannoma at the Liverpool Ocular Oncology Centre. Methods: Patients with choroidal schwannoma were identified by searching the computerised database of the Liverpool Ocular Oncology Centre. Results: The patients (3 males, 2 females) ranged in age from 15 years to 45 years. Three tumours were treated by enucleation, trans-scleral local resection, and combined bevacizumab and photodynamic therapy, respectively. Two were observed after confirmation of the diagnosis by biopsy. Conclusions: Choroidal schwannoma has a variety of clinical manifestations. Associated features include hard exudates, retinal feeder vessels and serous retinal detachment. Biopsy with immunohistochemistry is required for diagnosis. Tumours not amenable to resection may respond to photodynamic therapy.